TEORI KEADILAN (THEORY OF JUSTICE) Kajian dalam Perspektif Filsafat Hukum Islam Dan Barat - Fuji Rahmadi P (State of Islamic Institute Langsa, 2018)
There is not any emphasis on the value of justice greater than this matter (that God sent His apostles and sent down His Book) to bring about justice. In the name of justice the books were revealed and the Apostles were sent. Because of this justice, the life of heaven and earth is also upheld. The evolution of the philosophy of law, which is inherent in the whole philosophy evolution, revolves around the certain problems that arise repeatedly. Among these problems, the most frequent discourse is the issue of justice in relation to the law. It happens because laws or regulations should have been fair, but in fact they often don't. Keywords: justice, philosophy, law, perspective, West, Islam Abstrak: Tiada penekanan akan nilai keadilan yang lebih besar dari pada perkara ini (bahwa Allah mengutus para rasul-Nya dan menurunkan Kitab-Nya) untuk mewujudkan keadilan. Maka dengan atas nama keadilan kitab-kitab diturunkan dan para Rasul diutus. Dengan keadilan ini pula tegaklah kehidupan langit dan bumi. Evolusi filsafat hukum, yang melekat dalam evolusi filsafat secara keseluruhan, berputar di sekitar problema tertentu yang muncul berulang-ulang. Di antara problema ini, yang paling sering menjadi diskursus adalah tentang persoalan keadilan dalam kaitannya dengan hukum. Hal ini dikarenakan hukum atau aturan perundangan harusnya adil, tapi nyatanya seringkali tidak. Kata Kunci: keadilan, filsafat, hukum, perspektif, Barat, Islam